Studi Pemberitaan Konflik Rusia Dan Ukraina Di Tribun News Menurut Persepsi Organisasi Kepemudaan Islam UIN Raden Fatah Palembang - Adila Misbahussururi Adila; Amin Sihabudin; Anang Walian (CV. ITTC INDONESIA, 2023)
This study aims to determine the perceptions of Islamic youth organizations at UIN Raden Fatah regarding reporting on the conflict between Russia and Ukraine in the Tribun News.com media. The method used in this research is a quantitative descriptive method. The sample in this study were members of the PMII and HMI organizations, totaling 65 people, namely 40 people from PMII and 25 people from HMI. The results of the analysis of the data processing process found that almost all members of the HMI organization had the perception that the Tribun.News media had reported the conflict between Russia and Ukraine very well and met good quality standards for reporting, and furthermore the perceptions of respondents from PMII were also almost the same, there were more PMII organization members think that Tribun.News has been very good at reporting on the conflict between Russia and Ukraine, and they rate any news content positively about the conflict.